One last puff? Public smoking bans and smoking behavior - Silke Anger; Michael Kvasnicka; Thomas Siedler (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
This paper investigates the short-term effects of public smoking bans on individual smoking behavior. In 2007 and 2008, state-level smoking bans were gradually introduced in all of Germany's sixteen federal states. We exploit this variation in the timing of state bans to identify the effect that smoke-free policies had on individuals' smoking propensity and smoking intensity. Using rich longitudinal data from the German Socio-Economic Panel Study, our difference-in-differences estimates show that the introduction of smoke-free legislation in Germany did not change average smoking behavior within the population. However, our estimates also point to important heterogeneous effects. Groups that go out more often, and hence are more exposed to the constraints of public smoking bans in everyday life, did adjust their smoking behavior. Specifically, we find that young, unmarried individuals, and those living in urban areas are groups that are both less likely to smoke and smoke less intensively following the introduction of public smoking bans. Furthermore, effects on individual smoking habits proved stronger in states that had more strict smoking bans. Public smoking bans, therefore, have important health benefits over and above the reduction in exposure of non-smokers to second-hand smoke that is their immediate and prime objective.
Keywords: I12; K32; I18; C33; 330; Public smoking bans; smoking; cigarette consumption; treatment effects; Rauchen; Wirkungsanalyse; Konsumentenverhalten; Deutschland